Analysis of capital market reaction to the 2024 Prabowo-Gibran inauguration on Indonesian Stock Exchange - Putra, I Komang Gita; Sumiari, Kadek Nita; Dewi, Ni Komang Urip Krisna (Journal of Applied Sciences in Accounting, Finance, and Tax, 2025)
The Free Nutritious Meals (MBG) program was one of Prabowo-Gibran’s flagship programs during the 2024 presidential and vice-presidential election campaign. The inauguration of the Prabowo-Gibran president and vice-president was a highly anticipated event not only by the public, but also by investors who believed it would impact the Indonesian capital market. This study aimed to examine the market reaction to the inauguration of the Prabowo-Gibran president and vice-president among companies in the consumer non-cyclical food and beverage subsector on the IDX. The capital market reaction was proxied by trading volume activity and abnormal returns. The researchers used a population of companies in the consumer non-cyclical food and beverage subsector and obtained a sample of 91 companies using a purposive sampling method. The observation period for the reaction was three days before and three days after the event from 16 October 2024 until 23 October 2024. Testing was conducted using the One Sample Kolmogorov-Smirnov test for normality and the Wilcoxon Signed Rank Test for hypothesis testing using SPSS 26. The study found that there is no difference in average trading volume activity before and after the event